2019
DOI: 10.1016/j.ast.2019.04.047
|View full text |Cite
|
Sign up to set email alerts
|

A rod-linear cascade model for emulating rotor-stator interaction noise in turbofans: A numerical study

Abstract: a r t i c l e i n f o a b s t r a c tThis manuscript presents a rod-linear cascade model for emulating rotor-stator interaction noise. The model is intended as a test platform for studying noise mitigation techniques for a turbofan fan stage, while it also extends the classical rod-airfoil configuration by considering a row of blades based on realistic geometrical details. The rod-linear cascade model consists of a rod positioned upstream of a 7-blade linear cascade, such that the rod wake impinges onto the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…This vortex generation method is a classical approach to flow interaction problems. Cylindrical bluff bodies are frequently used to mimic stage interaction problems in turbomachinery [10,11]. This approach is preferred because it is more representative of the actual flow in a combustor where coherent vortices are convected with the mean flow.…”
Section: Introductionmentioning
confidence: 99%
“…This vortex generation method is a classical approach to flow interaction problems. Cylindrical bluff bodies are frequently used to mimic stage interaction problems in turbomachinery [10,11]. This approach is preferred because it is more representative of the actual flow in a combustor where coherent vortices are convected with the mean flow.…”
Section: Introductionmentioning
confidence: 99%
“…In the studies of probe-compressor interaction mentioned above, the probe is usually simplified as a strut or cylinder. Teruna et al's numerical results [6] showed that the blade surface pressure fluctuates greatly when the upstream cylinder wakes impinge on the compressor blade. The blade resonance may occur under the influence of large-scale Kármán vortex street shedding from upstream cylinders [7,8].…”
Section: Introductionmentioning
confidence: 99%